Analysis of Appraisal System in News Text â€œBerebut Vaksinâ€: A Study of Systemic Functional of Linguistic - Andi Indah Yulianti; Dwiani Septiana; Darmawati Majid Rosni (Indonesian Language Education and Literature, 2021)
This study aims to describe the type, form, influence, and reasons for the attitude used in the news text. This qualitative descriptive research data comes from the news text on medcom.id entitled "Scrambling for Vaccines." The analysis results show that there are three types of attitudes: affection, judgment, and appreciation. Appraisal items in news texts are classified into several forms of attitude: epithets, attributes, circumstances, modal adjuncts, words, and phrases. This attitude affects the subjectivity of the writer. Furthermore, the analysis results explain that the news writers try to give a fair opinion based on their views, perspectives of informants, and other news regarding the distribution of vaccines. It identifies many forms of negative appreciation and judgment. News writers tend to negatively view vaccine manufacturers, countries globally, the global population, and Indonesian citizens.Penelitian ini bertujuan untuk mendeskripsikan jenis, bentuk, pengaruh, dan alasan attitude yang digunakan dalam teks berita. Data penelitian deskriptif kualitatif ini berasal dari teks berita di medcom.id yang berjudul â€œBerebut Vaksinâ€. Hasil analisis menunjukkan bahwa ada tiga jenis attitude: afeksi, penilaian, dan apresiasi. Item apraisal dalam teks berita diklasifikasikan ke dalam beberapa bentuk sikap: epitet, atribut, keadaan, modal adjunct, kata, dan frase. Attitude ini memengaruhi subjektivitas penulis. Selanjutnya, hasil analisis menjelaskan bahwa penulis berita berusaha untuk memberikan pendapat yang adil, berdasarkan pandangan diri, perspektif informan, dan berita lainnya mengenai pendistribusian vaksin. Hal ini mengidentifikasi banyak bentuk apresiasi negatif dan penilaian. Penulis berita cenderung memiliki pandangan negatif terhadap produsen vaksin, negara di dunia, populasi global, dan warga negara Indonesia.